Fabrication of tissue engineered osteochondral grafts for restoring the articular surface of diarthrodial joints - Roach, Brendan L. (Methods, 2015)
Osteochondral allograft implantation is an effective cartilage restoration technique for large defects (>10 cm(2)), though the demand far exceeds the supply of available quality donor tissue. Large bilayered engineered cartilage tissue constructs with accurate anatomical features (i.e. contours, thickness, architecture) could be beneficial in replacing damaged tissue. When creating these osteochondral constructs, however, it is pertinent to maintain biofidelity to restore functionality. Here, we describe a step-by-step framework for the fabrication of a large osteochondral construct with correct anatomical architecture and topology through a combination of high-resolution imaging, rapid prototyping, impression molding, and injection molding.